2012
DOI: 10.1097/ico.0b013e318245c02a
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Keratitis After Boston Type 1 Keratoprosthesis Implantation

Abstract: Infectious keratitis after Kpro can occur even when patients are on vancomycin and a fourth-generation fluoroquinolone for prophylaxis. Fungal organisms are a growing cause for concern, and we present the details of the first reported case of ocular D. constricta. The evolution of our management and prophylaxis strategy for fungal keratitis after Kpro implantation is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 23 publications
5
44
1
2
Order By: Relevance
“…But the common factor was the symptom of pain in all cases compared to only 25 % patients complaining pain in post-cataract surgery endophthalmitis in the endophthalmitis vitrectomy (EVS) study [7]. The incidence of endophthalmitis at 11.1 % in our study was between other reported incidences in literature (11.4 % and 12 [5,6]-2.5 % and 2.4 % [3,5,6,8,9]), but 158-fold higher than the incidence of endophthalmitis after cataract surgery in our institute (0.07 % culture proven endophthalmitis [10]) and 55-fold higher than penetrating keratoplasty (0.2 %). Other differences included equal distribution of bacterial and fungal infection; but this cannot be concluded emphatically due to small numbers (Table 2).…”
Section: Discussionsupporting
confidence: 63%
“…But the common factor was the symptom of pain in all cases compared to only 25 % patients complaining pain in post-cataract surgery endophthalmitis in the endophthalmitis vitrectomy (EVS) study [7]. The incidence of endophthalmitis at 11.1 % in our study was between other reported incidences in literature (11.4 % and 12 [5,6]-2.5 % and 2.4 % [3,5,6,8,9]), but 158-fold higher than the incidence of endophthalmitis after cataract surgery in our institute (0.07 % culture proven endophthalmitis [10]) and 55-fold higher than penetrating keratoplasty (0.2 %). Other differences included equal distribution of bacterial and fungal infection; but this cannot be concluded emphatically due to small numbers (Table 2).…”
Section: Discussionsupporting
confidence: 63%
“…This was possibly due to the biodegradation or dysfunction of SESB2V peptide in the corneal stroma. Our results are encouraging for the early postoperative period, but bacterial endophthalmitis may occur months or years after the placement of a device (4)(5)(6). Hence, future work should examine the role of AMPs combined with a controlled drug delivery system, e.g., nanoparticles or biodegradable films.…”
Section: Discussionmentioning
confidence: 97%
“…Devices that penetrate the skin or those that are within tissues, e.g., the cornea, present the highest risks for infection (2,3). Endophthalmitis, a severe panocular infection, remains one of the most devastating complications after the implantation of any artificial corneal device, e.g., intracorneal stromal rings to correct refractive errors (4,5), Boston keratoprosthesis (6)(7)(8), and osteo-odonto keratoprosthesis (OOKP) (9, 10) used to restore vision in patients with end-stage corneal blindness. Patients with endophthalmitis present with discharge, lid swelling, pain, reduced vision acuity, implant erosion, or exposure (11).…”
mentioning
confidence: 99%
“…Ezek közül két esetben Rhodococcus equi okozta a fertőzést. A beül-tetés után elhúzódó lokális profilaktikus vancomycin-és moxifloxacinkezelést javasolnak, azonban, ha fertőzéses szövődményt észlelnek, felmerül a keratoprotézis eltávo-lítása vagy cseréje [4].…”
Section: Megbeszélésunclassified
“…A HIV terjedésétől kezdve egyre gyakrabban diagnosztizálták, legtöbb esetben immunhiányos állapotban lévő betegeken, például szervtranszplantáltaknál és daganatos betegeknél [3]. Gyó-gyászatban használt implantátumokkal összefüggésben csak kevés publikáció született [4,5]. Mozgásszervrend-szeri sebészetben használt implantátumhoz társuló fertőzésről pedig, tudomásunk szerint, eddig még nem szá-moltak be.…”
unclassified